Flexible silicon photonic transmitter with segmented modulator and 32 nm CMOS driver IC - Huynh, Tam; Dupuis, Nicolas; Rimolo-Donadio, Renato; Proesel, Jonathan; Gill, Doug; Baks, Christian; Rylyakov, Alexander; Schow, Clint; Green, William; Lee, Benjamin (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We present a novel silicon photonic transmitter including 90nm CMOS segmented modulator co-packaged with low power 32nm CMOS driver IC. Optical equalization is demonstrated for the first time with the multi-segment Mach-Zehnder modulator at 22Gb/s. OCIS codes: (130.4110) Modulator; (250.3140) Integrated optoelectronic circuits.
Conferencia
Keywords: CMOS; Circuitos; Óptica; Modulaciones; Fotónica